Investigation of carbon nanofiber supported iron catalyst preparation by deposition precipitation - van Thien Duc, N. (Trans Tech Publications Ltd, 2014)
An ammonia synthesis using magnetic field to replace Haber-Boschâs ammonia production is great technological challenge in novel magnetized catalysts area. The carbon nanofiber supported iron catalyst was prepared by modifying carbon nanofiber support surface and later using urea to precipitate iron nitrate by deposition precipitation. It was found that the particle size was in a range of 5-50nm and well dispersion of iron was shown by transmission electron microscopy. This was strongly influenced by alteration of carbon nanofiber surface from hydrophobic to hydrophilic and with high adsorption sites as oxygen functional groups and defects. The lower iron loading between 5 and 40wt, the lower iron accumulation and the narrower the particle size distribution of 10-20nm. The result suggests that the iron particles are in a good size range for iron catalyst activity for ammonia synthesis as reported by Morawski et.al and Figurski et.al authors. Â© (2014) Trans Tech Publications, Switzerland.